2017
DOI: 10.1063/1.4978773
|View full text |Cite
|
Sign up to set email alerts
|

Linear magnetoresistance in a topological insulator Ru2Sn3

Abstract: We have studied magnetotransport properties of a topological insulator material Ru2Sn3. Bulk single crystals of Ru2Sn3 were grown by a Bi flux method. The resistivity is semiconducting at high temperatures above 160 K, while it becomes metallic below 160 K. Nonlinear field dependence of Hall resistivity in the metallic region shows conduction of multiple carriers at low temperatures. In the high-temperature semiconducting region, magnetoresistance exhibits a conventional quadratic magnetic-field dependence. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
7
1
1
Order By: Relevance
“…In the field region below 0.2 T we see influence from the superconductinglike transition discussed in the Appendix. At 20 T the MR exceeds 100%, much higher than in a previous magnetotransport study 30 , and in our samples where the Sn mass loss was not compensated. This shows that the MR is, together with the temperature dependence of the resistivity, strongly dependent on the Sn content.…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…In the field region below 0.2 T we see influence from the superconductinglike transition discussed in the Appendix. At 20 T the MR exceeds 100%, much higher than in a previous magnetotransport study 30 , and in our samples where the Sn mass loss was not compensated. This shows that the MR is, together with the temperature dependence of the resistivity, strongly dependent on the Sn content.…”
Section: Resultscontrasting
confidence: 60%
“…As we discuss above, previous studies 26, [28][29][30]36,44 suggest a strong dependence of ρ(T ) in Ru 2 Sn 3 on the sample quality and composition. Notably, Kawasoko et al 36 have shown that creating Sn deficiency in polycrystalline Ru 2 Sn 3 samples leads both to a shift of the maximum in ρ(T ) to lower temperature and to an enhanced resistivity in the whole temperature range.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Это обстоятельство неизбежно приводит к появлению в низкочастотной оптической проводимости Ru 2 Sn 3 вклада от внутризонного поглощения за счет взаимодействия электромагнитной волны с электронами, локализованными вблизи фермиевской границы. Низкий уровень такого поглощения обусловлен малой концентрацией электронов проводимости, что соответствует результатам измерения электросопротивления данного соединения [8,16], величина которого на три порядка превышает значения данного параметра в хороших металлах.…”
Section: результаты и обсуждениеunclassified
“…β-IrSn 4 is a type-II superconductor with a much lower critical temperature of T C = 0.9 K [10]. Other important electronic properties have been found for the topological insulator Ru 2 Sn 3 which shows a semiconductor-metal transition along with a structural phase transition (tetragonal high-to orthorhombic low-temperature phase) [11][12][13]. The large linear magnetoresistance behavior of Ru 2 Sn 3 is similar to that of the recently reported hightemperature modification of RhSn 4 [14].…”
Section: Introductionmentioning
confidence: 99%